Tazreen Factory Fire : An Accident or Sheer Negligence? - Tamoli, Madhu (Prabandhan: Indian Journal of Management, 2016)
This case explored the Dhaka based garment Tazreen factory fire, which killed and injured a large number of people. Through this accident, the case investigated the poor working conditions in the garments industry of Bangladesh, which frequently puts the life of millions of workers in danger. Despite the fact that the garment industry has been the backbone of the country, the case exposed how the workers of Bangladesh are exploited socially and economically inside the factories. Highlighting the irresponsible nature of the managers of the factory during the tragedy, this case also sheds light on the negligent behavior of major Western brands that have an undeniable responsibility towards maintaining better safety conditions for the factory workers. Additionally, the case discussed about the unrest in the RMG sector added by the poor response of the government towards such mishaps and delaying the compensation to the fire victims.